Distribusi Pencabutan Gigi Berdasarkan Karakteristik Sosiodemografi pada Pasien RSGM Universitas Jember Periode Januari-Desember 2014 (Distribution of Tooth Extraction Based on Sociodemographic Characteristic of Dental Hospital of University of Jember Pat - Zulfa Fithri; Abdul Rochim; Zainul Cholid (Pustaka Kesehatan, 2017)
Background: The number of tooth extraction in Dental Hospital of Unversity ofJember increased on 2014. It might be caused by inapropriate dental health program.Information about distribution of tooth extraction by sociodemographic characteristic isneeded to make apropriate dental health program to decrease the number ofextraction in Dental Hospital of University of Jember. Purpose: To find out thedistribution of tooth extraction by sociodemographic characteristic in Dental Hospitalof University of Jember patients on January-December 2014. Methods: A descriptiveresearch used medical records from new Dental Hospital of University of Jemberpatients experienced tooth extraction on January-December 2014 with completemedical record and were ≥17 years old. The data were divided into groups based onsociodemographic characteristic (age, sex, education level). The data of tooth type,number, and reason of tooth extraction were collected from each sociodemographiccharacteristic groups. The results were presented in graphics and tabels. Result andConclusion: Female, elderly, and basic education level had higher number of toothextraction. Periodontal disease was the main reason of tooth extraction in all groups.Posterior teeth, especially mandibular first molar, were more frequently extracted inthe most groups.Keywords: dental health program, sociodemographic, tooth extraction